A 3D‐Printed Hybrid Nasal Cartilage with Functional Electronic Olfaction. Issue 5 (10th January 2020) - Jodat, Yasamin A.; Kiaee, Kiavash; Vela Jarquin, Daniel; De la Garza Hernández, Rosakaren Ludivina; Wang, Ting; Joshi, Sudeep; Rezaei, Zahra; de Melo, Bruna Alice Gomes; Ge, David; Mannoor, Manu S.; Shin, Su Ryon
Abstract: Advances in biomanufacturing techniques have opened the doors to recapitulate human sensory organs such as the nose and ear in vitro with adequate levels of functionality. Such advancements have enabled simultaneous targeting of two challenges in engineered sensory organs, especially the nose: i) mechanically robust reconstruction of the nasal cartilage with high precision and ii) replication of the nose functionality: odor perception. Hybrid nasal organs can be equipped with remarkable capabilities such as augmented olfactory perception. Herein, a proof‐of‐concept for an odor‐perceptive nose‐like hybrid, which is composed of a mechanically robust cartilage‐like construct and a biocompatible biosensing platform, is proposed. Specifically, 3D cartilage‐like tissue constructs are created by multi‐material 3D bioprinting using mechanically tunable chondrocyte‐laden bioinks. In addition, by optimizing the composition of stiff and soft bioinks in macro‐scale printed constructs, the competence of this system in providing improved viability and recapitulation of chondrocyte cell behavior in mechanically robust 3D constructs is demonstrated. Furthermore, the engineered cartilage‐like tissue construct is integrated with an electrochemical biosensing system to bring functional olfactory sensations toward multiple specific airway disease biomarkers, explosives, and toxins under biocompatible conditions. Proposed hybrid constructs can lay the groundwork for functional bionic interfaces and humanoid cyborgs. Abstract : An odor‐perceptive nose‐like hybrid is developed using multi‐material 3D bioprinting. The mechanically robust cartilage‐mimetic tissue is integrated with a biosensing platform tunable to "sniff out" a wide range of chemical structures, such as explosives. This integrative approach lays the groundwork for functional bionic interfaces and humanoid cyborgs.